Study on the Genus Plectranthus (Lamiaceae) in Java: P. verticillatus, a captivating new alien species - Arifin Surya Dwipa Irsyam; Muhammad Rifqi Hariri; Muhammad Fabio Rayhan Kurniawan; Rina Ratnasih Irwanto (Biogenesis: Jurnal Ilmiah Biologi, 2023)
Plectranthus (Lamiaceae) is a popular ornamental plant all over the world. The study of the genus Plectranthus in Java was considered complete after the publication of Flora of Java Vol. II. Many authors, however, have reported the presence of numerous alien species on the island in recent years. The aim of this research is to provide current information on Plectranthus in Java, particularly the newly recorded alien species. The study was carried out using the free exploration method in the provinces of Banten, Jakarta, West Java, and East Java. We reported the first occurrence of P. verticillatus (L.f.) Druce in Java in this paper. The species is a succulent herb native to Southern Africa that has grown in popularity as an ornamental plant throughout the world. It is a newly discovered alien species to the Alien Flora of Java. The species appears to have escaped cultivation, with spontaneous populations found in Jatihandap and Cipadung, both in Bandung City. We also reported that P. verticillatus is the only member of Plectranthus found in Java in a recent taxonomic study. There is a description, photographs, botanical illustrations, and a brief discussion.